Faith community as a centre of liberationist praxis in the city - Hankela, Elina (HTS teologiese studies, 2014)
Theologians speak of the silence of churches’ prophetic voice in the ‘new’ South Africa, whilst the country features amongst the socio-economically most unequal countries in the world, and the urban areas in particular continue to be characterised by segregation. In this context I ask: where is liberation theology? I spell out my reading of some of the recent voices in the liberationist discourse. In dialogue with these scholars I, firstly, argue for the faith community to be made a conscious centre of liberationist debates and praxis. Secondly, I do this by suggesting two theoretical building blocks (i.e. critical deconstruction and radical friendship) for local faith communities that wish to grow in a liberationist fashion.